2021
DOI: 10.1016/j.mex.2021.101316
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the online objective structured clinical examinations in urology qualifying exam for urology residents in Indonesia during COVID-19 time

Abstract: This project aimed to assess the Online National Board of Urology Objective Structured Clinical Examination (OSCE) feasibility in evaluating candidates simultaneously from five urology training centers in Indonesia during the COVID-19 pandemic. Data were collected from two online OSCE simulation trials and the Online National Board of Urology OSCE. A self-administered questionnaire was used to assess examiners and candidates’ perception. The average final score of the Online OSCE was compared to previous face-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Our search yielded 306 potentially relevant articles with 13 articles remaining after title, abstract, and full-text screening ( Arrogante et al, 2021 ; Biolik et al, 2018 ; Boardman et al, 2021 ; Darr et al, 2021 ; Farrell et al, 2021 ; Hsia et al, 2021 ; Lara et al, 2020 ; Martinez et al, 2020 ; Nackman et al, 2006 ; Novack et al, 2002 ; Oliven et al, 2011 ; Scoular et al, 2021 ; Sihombing et al, 2021 ). The PRISMA flow diagram for this research question can be found in Figure 1 ( Page et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our search yielded 306 potentially relevant articles with 13 articles remaining after title, abstract, and full-text screening ( Arrogante et al, 2021 ; Biolik et al, 2018 ; Boardman et al, 2021 ; Darr et al, 2021 ; Farrell et al, 2021 ; Hsia et al, 2021 ; Lara et al, 2020 ; Martinez et al, 2020 ; Nackman et al, 2006 ; Novack et al, 2002 ; Oliven et al, 2011 ; Scoular et al, 2021 ; Sihombing et al, 2021 ). The PRISMA flow diagram for this research question can be found in Figure 1 ( Page et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 44 articles reporting practical assessment, 32 were conducted online, 16,24,25,34,37,38,49,51–58,62,64–71,75–82 4 were conducted in person 36,59,60,63 and 8 used a hybrid format of assessment 17,21,23,26,61,72–74 . Several competencies such as professionalism, clinical reasoning and history‐taking were assessed using OSCE; however, none of the OSCE conducted online could assess hands‐on skills.…”
Section: Resultsmentioning
confidence: 99%
“…All but 10 studies reported assessment within a single institution. The remaining 10 were either board examinations or national (Objective Structured Clinical Examination) OSCEs of different countries 18–27 …”
Section: Resultsmentioning
confidence: 99%
“…14 The effectiveness of web-based online exams has been demonstrated in various subjects. 15 Cor et al 16 conducted a study on the use of online interviews for selecting students entering pharmacy practice programs, which revealed that most students preferred online interviews over on-site interviews. Moreover, few students experienced technical or practical problems while completing exams remotely.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the outbreak of COVID‐19, people have been reluctant to travel, 13 making online re‐examination a preferred option, and reducing travel time and expenses 14 . The effectiveness of web‐based online exams has been demonstrated in various subjects 15 . Cor et al 16 .…”
Section: Discussionmentioning
confidence: 99%